ChemInform Abstract: A Catalyst‐Enabled Diastereodivergent Aza‐Diels—Alder Reaction: Complementarity of N‐Heterocyclic Carbenes and Chiral Amines. Issue 48 (10th November 2016) - Rong, Zi‐Qiang; Wang, Min; Chow, Chi Hao Eugene; Zhao, Yu
Abstract: The method represents the first complementarity of a chiral amine and an NHC catalyst offering an approach to either diastereomeric series of benzofuran‐fused δ‐lactams and dihydropyridines with excellent stereoselectivities.